Control devices in refrigeration system / Ahmad Fauzi Khalil and Jawan Undom - Khalil, Ahmad Fauzi; Undom, Jawan (1991)
By defination refrigeration is a process by which heat is removed from space to a place where it makes no difference whereas a system is an interaction or coordination devices design for a purpose(s). Now, most of the time refrigeration system is required to operate with a predetermined parameter. For instance at certain interval of time the refrigeration system may be required to generate part load. In this case the ability of the system to automatically change it refrigeration capacity in respond to load demand becomes very important. As such the operation of different system components or equipment may have to occur in a certain time sequence. The mode of operation of a system component may as well have to be periodically changed, as in defrosting or switching a heat purpose cycle.